English for Computer Science - Luzón Marco, Mª José (Textos Docentes, 2012)
Manual de la asignatura Inglés Técnico de la licenciatura de Ingeniería Informática. El texto, íntegramente en inglés, consta de 8 capítulos: 1) Expository/descriptive texts. 2) Reporting and narrating. Texts with a chronological sequence. 3) Processes and procedures: description of processes. 4) Processes and procedures: instructions. 5) Comparison and evaluation. 6) Predictions and hypoteses. 7) Argumentative texts. 8) Business correspondence. Cada capítulo consta de una introducción, un apartado de información lingüística y un conjunto de ejercicios.